Furcocercous cercariae shed by the freshwater snails Pila occidentalis (Mousson, 1887) and Biomphalaria pfeifferi (Krauss, 1848) in the Okavango Delta, Botswana. Issue 2 (27th May 2016) - Jansen van Rensburg, C; King, PH; van As, JG
Abstract : During July 2009 and 2010 surveys of snail-borne larval trematodes of the Okavango Delta floodplains and lagoons were undertaken. Cercaria mohemboense were shed by Pila occidentalis (Mousson, 1887) and Cercaria dubaensis and Cercaria indistinctus were shed by Biomphalaria pfeifferi (Krauss, 1848), respectively. Morphological descriptions of these fork-tailed cercariae are given, with suggestions on the possible life cycles of these parasites.